PERBANDINGAN TANAMAN JAGUNG DAN KACANG HIJAU PADA MUSIM KEKERINGAN DI GROBOGAN - Etik Irawati; Fianti Fianti; Upik Nurbaiti (Universitas Lambung Mangkurat, 2021)
Almost every year, most of Grobogan Regency experiences drought which can affect various fields including agriculture, where some of the people are farmers. This article aims to analyze the comparison of the secondary crops of maize and green beans during the drought season in the villages of Banjardowo, Plosorejo, and Mayahan, Grobogan Regency. This study used survey research involving 20 respondents (farmers) from the three villages. Data collection techniques, namely, observation, interviews, respondent questionnaires and documentation. The results of the interview showed that the interviewee planted green beans as a staple crop in both the rice-paddy-secondary crops and the rice-crops-bero cropping pattern. Cultivating green beans in the rice-crops-bero pattern, the farmers of the three villages planted them on broken land (nelo: Java) because of the high level of drought. The results from 20 respondents were seen from 6 aspects: 1) suitability of plants in the dry season. 2) Planting on the ground that is broken (Nelo: Java). 3) relatively water efficient. 4) High Income. 5) Pest resistance. 6) Abbreviations of the harvest period, namely the average yield of green bean plants is 87.04% while corn is 52.04%. The conclusion of this research is that green beans are a suitable alternative crop to be planted in the dry season.